1997
DOI: 10.1080/00224549709595415
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Self-Efficacy—Performance Linkage of Social—Cognitive Theory

Abstract: Past empirical research examining the relationship of self-efficacy perceptions and performance has had several limitations. Most studies were performed in the laboratory with tasks not directly related to individual work performance. As a consequence, many findings are not generalizable to individual work performance. This study tested the self-efficacy-performance model found in Bandura's social-cognitive theory in a work setting, with a sample of 776 American university employees, and with discriminant func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(63 citation statements)
references
References 27 publications
1
55
0
1
Order By: Relevance
“…Bandura (1982) defined selfefficacy as judgments individuals make about their competency to perform a defined task; he identified four sources of self-efficacy development-enactive mastery, modeling, verbal persuasion, and arousal. Various studies have found a positive relationship between pretraining self-efficacy and ultimate training mastery (Harrison, Rainer, Hochwarter, & Thompson, 1997;Holladay & Quinones, 2003;Mathieu, Martineau, & Tannenbaum, 1993). In terms of transfer outcomes, self-efficacy has been found to be positively related to transfer generalization and transfer maintenance across multiple studies (Chiaburu & Marinova, 2005;Ford, Smith, Weissbein, Gully, & Salas, 1998;Gaudine & Saks, 2004;Gist, 1989;Latham & Frayne, 1989;Mathieu, Tannenbaum, & Salas, 1992;Saks, 1995;Stevens & Gist, 1997;Tannenbaum, Mathieu, Salas, & Cannon-Bowers, 1991).…”
Section: Self-efficacymentioning
confidence: 99%
“…Bandura (1982) defined selfefficacy as judgments individuals make about their competency to perform a defined task; he identified four sources of self-efficacy development-enactive mastery, modeling, verbal persuasion, and arousal. Various studies have found a positive relationship between pretraining self-efficacy and ultimate training mastery (Harrison, Rainer, Hochwarter, & Thompson, 1997;Holladay & Quinones, 2003;Mathieu, Martineau, & Tannenbaum, 1993). In terms of transfer outcomes, self-efficacy has been found to be positively related to transfer generalization and transfer maintenance across multiple studies (Chiaburu & Marinova, 2005;Ford, Smith, Weissbein, Gully, & Salas, 1998;Gaudine & Saks, 2004;Gist, 1989;Latham & Frayne, 1989;Mathieu, Tannenbaum, & Salas, 1992;Saks, 1995;Stevens & Gist, 1997;Tannenbaum, Mathieu, Salas, & Cannon-Bowers, 1991).…”
Section: Self-efficacymentioning
confidence: 99%
“…It is clear that computer selfefficacy promotes performance and lessens computer induced anxiety (Burkhardt & Brass 1990;Harrison & Rainer 1997) among users and that teachers' computer self-efficacy is a major influence shaping their patterns of computer use (Albion, 2001). In addition, computer self-efficacy significantly predicted pre-service teachers' ability to integrate technology use in the classroom ( Positive disposition towards computers is a prerequisite and catalyst to acquiring a high level of computer literacy and successful pedagogical use of technology (Francis, Katz, & Jones, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…An individual with high levels of self-efficacy not only have a greater commitment to organization, but also higher level of job satisfaction (Luthans et al, 2006). Employees had higher self-efficacy which was found to be predictor of future performance and skill development (Harrison et al, 1997). The right amount of self-efficacy is said to instigate sufficient effort which in turn will produce desirable health and satisfaction outcomes (Stajkovic & Luthans, 1998).…”
Section: Conclusion and Recommendationmentioning
confidence: 99%